A modelling methodology for the HTML knowledge base. (2016) - Liu, Limin
The hypertext markup language (HTML) has taken an irreplaceable position in the field of the internet. In this study, the complicated text-based HTML syntax is modelled as a shareable and computable knowledge base (KB). The proposed modelling methodology is sound and complete because it covers all constraints and semantics defined in the HTML. The result of the modelling methodology is a KB with a class hierarchy, constraints, and inference rules. It is programming language independent that can be used by any language with access interfaces to a KB. Based on the HTML KB, one can develop various tools and intelligent systems with all the advantages that KB system is promised to provide. For demonstration purpose, an expert system, the web content accessibility guidelines (WCAG) validation system, was built. It validates whether a web page meets the WCAG regulation and the HTML KB serves as a shareable KB in the system.